Utility-based barter trade incentive scheme in opportunistic network - Jian-sheng YAO; Chun-guang MA; Qi YUAN (Tongxin xuebao)
In opportunistic networks,existing simple barter trade (SBT) incentive scheme degraded the network performance due to the blindly caching strategy.So a utility-based barter trade (UBT) incentive mechanism was proposed.In the UBT scheme,nodes cache messages by predicting their future encounters and the probability that the encounters forward these messages to their destinations,which improved the caching efficiency and the network performance.Simulated results show that,compared with SBT,UBT can obtain higher delivery ratio and lower delay by less network cost and effectively motivate nodes’ cooperation as well.